All for a Cleaner School and Conscious Students - Rizzon, Mariluza Zucco (Scientia cum Industria, 2014)
This article reports the development of a project conducted by high school students in a public school of San Marcos, RS. The project involved teachers and students for cleaning and maintaining the school and also for developing the skills students with respect to environmental education. Several steps were necessary to achieve our goals, since environmental awareness, cleaning and garbage collection in school environments, reorganization of flowerbeds and planting seedlings (ornamentals, herbs for teas and spices), recycling craft activities, painting and even beautification of the classrooms. It was visible the importance of implementing the project, because at the end, all the students were engaged and learned to work as a team, to value and respect each other and the environment in which we live; and as citizens become more responsible for their actions. The project results indicated a significant relationship among the curriculum components, promoting the interdisciplinarity. It is worth noting that the school environment was more pleasant, clean and cozy. http://dx.doi.org/10.18226/23185279.v2iss2p52